Penilaian Sumber Pencemar Non Logam di Waduk Asin Pusong Kota Lhokseumawe Berdasarkan Analisis Multivariat - Riri Ezraneti; Syahrial Syahrial; Erniati Erniati (Universitas Diponegoro, 2021)
Human anthropogenic activities have resulted in an important transformation in the aquatic environment for decades, so the study of the assessment of non-metallic pollutant sources in the salty reservoir Pusong in Lhokseumawe City was conducted in October 2020 which was reviewed based on multivariate analysis. The study aims to find out the source of non-metallic pollutants in the salt reservoir waters of Pusong Kota Lhokseumawe with the collection of primary data conducted by observation at five observation stations, where water samples are taken using van dorn water sampler at a depth of ± 0 – 1 m with three repetitions per station. The results showed that non-metallic contaminants of total ammonia nitrogen, nitrate, and phosphate had exceeded the established quality standards (>5.00 mg/L, >0.30 mg/L, >0.008 mg/L and >0.015 mg/L), then based on PCA analysis, eigenvalues of each variable indicate the formation of two new components namely Component 1 consisting of non-metallic nitrate contaminants and total nitrogen ammonia (3.05), while Component 2 consists of non-metallic contaminants total coliform and BOD5 (1.93) with a data diversity of 82.99%. Besides, non-metallic contaminants of total nitrogen ammonia, as well as phosphates, have a significant relationship to temperature parameters, while non-metal nitrate contaminants have significant links to pH parameters, turbidity, and salinity. Furthermore, the complexity of the study area between observation stations based on CA analysis was divided into two groups, the first group consisted of Stations 2, 4, and 5 with non-metallic contaminants source nitrate, BOD5 as well as total coliform, while the second group consisted of Stations 1 and 3 with non-metallic contaminants of total ammonia nitrogen, phosphate, and surfactants. Kegiatan antropogenik manusia telah menghasilkan transformasi penting dalam lingkungan akuatik selama beberapa dekade, sehingga kajian penilaian sumber pencemar non logam di waduk asin Pusong Kota Lhokseumawe dilakukan pada bulan Oktober 2020 yang ditinjau berdasarkan analisis multivariat. Kajian bertujuan untuk mengetahui sumber pencemar non logam di perairan waduk asin Pusong Kota Lhokseumawe dengan pengumpulan data primernya dilakukan secara observasi di lima stasiun pengamatan, dimana sampel air diambil menggunakan van dorn water sampler pada kedalaman ± 0–1 m dengan tiga kali pengulangan setiap stasiunnya. Hasil kajian memperlihatkan bahwa sumber pencemar non logam total amonia nitrogen, nitrat maupun fosfat sudah melebihi baku mutu yang telah ditetapkan (>5.00 mg/L, >0.30 mg/L, >0.008 mg/L dan >0.015 mg/L), kemudian berdasarkan analisis PCA, nilai eigen dari masing-masing variabel mengindikasikan adanya pembentukan dua komponen baru yaitu Component 1 terdiri dari sumber pencemar non logam nitrat dan total amonia nitrogen (3.05), sedangkan Component 2 terdiri dari sumber pencemar non logam total coliform dan BOD5 (1.93) dengan keragaman datanya sebesar 82.99%. Selain itu, sumber pencemar non logam total amonia nitrogen maupun fosfat memiliki hubungan yang signifikan terhadap parameter suhu, sedangkan sumber pencemar non logam nitrat memiliki hubungan yang signifikan terhadap parameter pH, kekeruhan dan salinitas. Selanjutnya, kompleksitas wilayah studi antar stasiun pengamatan berdasarkan analisis CA terbagi atas dua kelompok, kelompok pertama terdiri dari Stasiun 2, 4 dan 5 dengan sumber pencemar non logam nitrat, BOD5 serta total coliform, sedangkan kelompok kedua terdiri dari Stasiun 1 dan 3 dengan sumber pencemar non logam total amonia nitrogen, fosfat serta surfaktan.